A Remotely Controlled Integrated Weapon Platform Developed on the Basis of Long-Term Experience and Competence - Krzysztof BIELAWSKI (Zdalnie sterowana, zintegrowana platforma uzbrojenia opracowana na bazie wieloletnich doświadczeńi posiadanych kompetencji, 2023)
For two decades, AREX Sp. z o.o. (Gdynia, Poland), belonging to WB Group (Warsaw, Poland), has been dealing with special-purpose production, in particular mechatronics, and its solutions are used in electromechanical accessories for 155 mm KRAB gun-howitzers and 120 mm RAK self-propelled wheeled gun-mortars. The operations of WB Group on international markets has given a boost to its further development. The solutions of the remotely controlled weapon platform presented in this paper can be adapted to weapons with ammunition fed from the left or right side, owing to the self-diagnostics and verification system as well as the modular design. The intention of the designers was to create functional and intuitive equipment that allows the operator to focus on firing operations. The remotely controlled weapon platform is also equipped with covering capacity, such as smoke grenades, and is also electrically operated, can be operated manually in emergencies, is intended for installation on various combat vehicles and is remotely controlled by the operator remaining inside the vehicle compartment, which ensures full armoured protection against enemy direct fire. Remote control is based on two operating components – a fire control unit and a control grip. Additionally the system is capable of remote weapon loading, weapon cocking, and firing. Tracking and remote controlling capabilities of the integrated weapon platform ensure high probability of hitting stationary and moving targets during the first round, and the platform can be operated manually as required.
Keywords: Konstrukcja zintegrowanej platformy uzbrojenia